Anserine reduces mortality in experimental sepsis by preventing methylglyoxal-induced capillary leakage - Schmoch, Thomas; Gallenstein, Nadia; Peters, Verena; Bartosova, Maria; Uhle, Florian; Kummer, Laura; Mair, Anian; Krauser, Ute; Feißt, Manuel; Nawroth, Peter Paul; Weigand, Markus A.; Schmitt, Claus P.; et al. (EBioMedicine, 2025)
BACKGROUND: We previously identified methylglyoxal as a biomarker for early identification and outcome prediction in human sepsis. We hypothesised that methylglyoxal causally impacts disease severity, and the methylglyoxal-scavenging dipeptide anserine can attenuate the detrimental effects of methylglyoxal. - METHODS: Using a translational approach, secondary analyses of two observational trials were performed to test the initial hypotheses. Afterwards, these results were re-evaluated in different murine models of experimental sepsis in vivo. The detrimental effects of methylglyoxal as well as the underlying mechanisms were further assessed in vitro using transendothelial electrical resistance measurements, fluorescence-activated cell sorting analyses, cytokine assays, gene expression analyses, and enzyme activity assays, as well as immunofluorescence and immunohistochemistry staining. - FINDINGS: The secondary analyses confirmed methylglyoxal as an independent marker associated with increased mortality within the first 48 h after sepsis onset and high catecholamine and fluid requirements in the first 24 h after sepsis onset. In the sepsis models, methylglyoxal-derived carbonyl stress significantly contributed to the development of capillary leakage by disrupting endothelial barrier-forming proteins. Mechanistically, a pathway involving the receptor of advanced glycation end products and mitogen-activated protein kinase was identified. The methylglyoxal-scavenging dipeptide anserine (β-alanyl-N-methylhistidine) reduced methylglyoxal-induced advanced glycation end-product formation and disruptions of junctional complexes in vitro. Moreover, anserine reduced capillary leakage and mortality in vivo. - INTERPRETATION: Methylglyoxal causally contributes to capillary leak formation and mortality in experimental sepsis, which can be mitigated by anserine. Therefore, anserine represents an innovative therapeutic option for the treatment of septic shock. - FUNDING: German Research Foundation (grant number BR 4144/2-1).